2011
DOI: 10.1107/s090744491102405x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor-bound structures of human pyruvate dehydrogenase kinase 4

Abstract: The mitochondrial pyruvate dehydrogenase complex (PDC) catalyzes the oxidative decarboxylation of pyruvate to acetyl-CoA. PDC activity is tightly regulated by four members of a family of pyruvate dehydrogenase kinase isoforms (PDK1-4), which phosphorylate and inactivate PDC. Recently, the development of specific inhibitors of PDK4 has become an especially important focus for the pharmaceutical management of diabetes and obesity. In this study, crystal structures of human PDK4 complexed with either AMPPNP, ADP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…In contrast to radicicol, M77976 ( Fig. 4H ) is developed as a PDK4-specific inhibitor [ 65 ]. It also binds to the same domain; however, the mechanism of action is different from radicicol.…”
Section: Effects Of the Small Molecular Pdk Inhibitors On Metabolic Dmentioning
confidence: 99%
“…In contrast to radicicol, M77976 ( Fig. 4H ) is developed as a PDK4-specific inhibitor [ 65 ]. It also binds to the same domain; however, the mechanism of action is different from radicicol.…”
Section: Effects Of the Small Molecular Pdk Inhibitors On Metabolic Dmentioning
confidence: 99%
“…[332] Very recently, pyrazole derivative M77976 ( 100 ), identified by in vitro screening, was crystalized with human PDK4 and it was found to bind to the ATP binding site of this enzyme and to inhibit it with an IC 50 value of 648 μM (under the same conditions, radicicol 95 displayed an IC 50 of about 1 mM). [333] …”
Section: Glycolytic Effectors As Potential Targets In Cancer Therapymentioning
confidence: 99%
“…3 and Table S3, a greater abundance of glycolysis enzymes suggested that glucose metabolism was improved in A100-8. Dihydrolipoamide acetyltransferase (spots 71 and 72) and dihydrolipoamide dehydrogenase (spots 73 and 74), acting at the end of the glycolytic pathway, catalyze the oxidative decarboxylation of pyruvate, transferring the acetyl group to CoA [18]. Malate dehydrogenase (spots 77, 78 and 79) and pyruvate carboxylase (spot 89) help the reversible oxidation of malate and pyruvate to oxaloacetate which can be converted to aspartate [19,20].…”
Section: Glycolysis and Tca Cycle Peptidesmentioning
confidence: 99%